Participatory Guarantee Systems, a more inclusive organic certification alternative? Unboxing certification costs and farm inspections in PGS based on a case study approach - Kaufmann, Sonja; Hruschka, Nikolaus; Vogl, Christian R. (Frontiers in Sustainable Food Systems, 2023)
The importance of Participatory Guarantee Systems (PGS) as an alternative organic certification to third-party certification (TPC) has grown remarkably in recent years. PGS are argued to be less costly than TPC, and adopt the exchange of advice and knowledge as a key element of farm inspections. For these reasons, PGS are promoted as being more accessible for smallholder farmers in low-income countries and as a tool for supporting organic conversion and standard compliance, and ultimately contributing to food system sustainability. PGS certification costs have not yet been studied thoroughly and empirical studies on PGS farm inspections are rare. This paper applies a mixed-methods case study approach in a Costa Rican PGS initiative and explores explicit and implicit PGS certification costs and PGS farm inspections. The framework for studying actor participation in PGS (Kaufmann et al. 2020) and transaction cost theory were used as the theoretical foundation. Semi-structured interviews (n=11), PGS member surveys (n=17) and participant observations of PGS farm inspections (n=11) were conducted and complemented with data from internal documents and informal interviews. The results showed that reduced explicit costs for PGS certification were accompanied by substantial implicit costs in terms of the time dedicated to the PGS certification process. These implicit costs were largely attributed to the legal requirements for PGS, and were borne by only a few members, resulting in differences in total certification costs between PGS members. Despite legal formalization, information exchange was an important part of PGS farm inspections. Against the backdrop of small audit teams and low participation in farm inspections, PGS members implementing farm inspections nurtured transparency and an exchange of experience within the PGS. The study provides novel insight into PGS, and defines cost components and PGS characteristics affecting PGS certification costs that may also be relevant to other PGS initiatives and related fields of action.